Edukasi Manfaat Tanaman Piperaceae dan Pelatihan Pembuatan Hand Sanitizer Alami kepada Siswa SMK Farmasi Surabaya - Meyke Herina Syafitri; Mercyska Suryandari; M.A. Hanny Ferry Fernanda (Pusat Riset dan Inovasi Nasional, 2023)
Betel leaves contain phenols that function as powerful antiseptics. Hand sanitizer (HS) is a product that can kill parasites on the hands and is easy to use. Therefore, in this event, education will be provided to the students of SMK Farmasi Surabaya regarding the benefits of betel leaves, followed by a training session on making hand sanitizers containing extract. The participant's level of understanding is evaluated by comparing the scores obtained before and after receiving information from the speaker. A questionnaire is given to allow participants to evaluate the overall conduct of the event, and they are invited to try the hand sanitizers prepared by the team. The results show that 76% of the participants achieved higher scores, 24% maintained the same scores, and none of the participants received lower scores compared to the pre-test. Overall, the participants expressed that the event was very beneficial.